'The heart has caught me': Anger metaphors in Likpakpaln (Konkomba). (10th September 2021) - Bisilki, Abraham Kwesi; Yakpo, Kofi
Abstract : We provide a first documentation and analysis of anger metaphors in Likpakpaln, a little-studied Mabia (Gur) language, primarily spoken in Northern Ghana. We adopt Conceptual Metaphor Theory as the analytical framework for this study. The study of emotional body-part metaphors and their lexicalisation patterns in Likpakpaln is interlaced with nominal and clausal morphosyntax as well as grammatical relations. Anger is conceptualised in terms of liŋuul 'heart' and we identify five types of clause structures in which anger expressions occur in Likpakpaln. Further, we make out four metaphorical conceptualisations. In an areally prominent conceptualisation that we term ANGER IS HUMAN-LIKE, liŋuul 'heart' is anthropomorphised as a human-like agent who can 'catch', 'hold', 'kill', or 'eat' a person. Other metaphorical conceptualisations are ANGER IS HEAT, AN ANGRY PERSON IS A PRESSURISED CONTAINER, and THE BODY IS A CONTAINER FOR ANGER. All in all, metaphors of anger in Likpakpaln show cross-cultural correspondences and culture-specific construals, thus providing evidence for the cultural embodied prototype theory. The Likpakpaln data also reflects a departure from some general tendencies. For instance, the coding of positive and negative emotion concepts in Likpakpaln is nuanced by the use of particular synonyms of the heart rather than by the selection of different body parts.